New Paradigms in Internet Computing - Patnaik, Srikanta.; Tripathy, Piyu.; Naik, Sagar. (Advances in Intelligent Systems and Computing,, 2013)
The renaissance of internet has reached the mainstream that is named as Web 2.0. People are now using the web to build things they have never thought of earlier. Experts take a step forward to what we contribute, and extend it and give back to the society, i.e. really the boon of internet computing. It has revolutionized the current business environment, not as a mere computing tool, but offers versatile services and increase the productive flow of information. It is a new dimension in computing systems by which companies can curtail their operating expenses, by hosting and operating through the internet. Now the users can access the required information by means of any device connected with an internet. The challenge ahead for implementing this versatile system is that the software and technology has to be developed and deployed simultaneously vis-a-vis safeguarding the security and privacy of information. This book encompasses various research and developments in Internet technology and put in the context of New Paradigms in Internet Computing. This includes chapters from academic research community as well as industry experts in the area of business models based on Software, Protocols, Supply Chain Management, Security and also Cloud Computing.